2020
DOI: 10.3390/jcm9113651
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Recurrent Emergency Department Visits among Patients with Crohn’s Disease: A Retrospective Study

Abstract: Patients with Crohn’s disease (CD) are frequently subject to symptoms causing them to seek medical care in emergency departments (ED). Recurrent ED visits are frequent after initial discharge. We aimed to identify the characteristics of patients with Crohn’s who tend to have recurrent visits to the ED. We created an electronic data repository of all patients with inflammatory bowel diseases who visited the ED in our tertiary medical center during the period 2012–2018. For this study, we retrieved consecutive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…None of these studies specifically examined recurrent short‐term ED utilization after an initial ED encounter 11 . A tertiary care study from Israel did find that abnormal clinical markers, including laboratory values and vital signs, were associated with increased risk of recurrent ED use among patients with CD 12 . There is limited understanding of how additional sociodemographic and clinical characteristics, and specifically, occurrence of post‐ED follow care, might be associated with recurrent ED utilization among patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…None of these studies specifically examined recurrent short‐term ED utilization after an initial ED encounter 11 . A tertiary care study from Israel did find that abnormal clinical markers, including laboratory values and vital signs, were associated with increased risk of recurrent ED use among patients with CD 12 . There is limited understanding of how additional sociodemographic and clinical characteristics, and specifically, occurrence of post‐ED follow care, might be associated with recurrent ED utilization among patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…This can take a toll on patient well-being and healthcare in terms of delayed diagnosis of complications and economic cost, respectively. Mahajna et al [ 6 ] demonstrated a 60% hospitalization rate of all patients with CD-related complaints presenting to the emergency department (ED) and a considerable 17.4% 30-day re-visit rate of those who were discharged. Notably, the factors associated with returning to the ED were tachycardia and anemia.…”
mentioning
confidence: 99%